(untitled) (Research, Society and Development, 2022)
The Caatinga is highly heterogeneous, many species being found in their regions. Much of anurofauna this area is commonly found in many open environments. In the present study both the diversity and the temporal occurrence of frogs were determined to Bela Vista Lagoon, located in the municipality of Cuité, Paraíba. 4 areas for sampling were marked, these being covered slowly by hiking. The naturalistic observations were conducted from May 2012 until April 2013 Methods of visual and auditory search were used to simultaneously capture and frequency of species. 6 frog species belonging to 4 genera were found distributed in three families: Bufonidae (2 species), Hylidae (2 species) and Leptodactylidae (2 species). Site 1 showed a wealth of three species, the other areas had a wealth equivalent of 5 species each. The anurofauna recorded high occupancy presented to water bodies and low associations zones altered by man. Nonparametric estimators, calculated for the 36 surveys for the pond Bela Vista, not reached its asymptote, but the Bootstrap model showed a tendency toward stabilization. Among the four sampled areas, Area 2 was the one with the highest diversity, areas 3 and 4 presented the lowest diversity, this fact being related to high dominance of species Rinnella jimi. Regarding the temporal distribution, amphibians showed up influenced by temperature and rainfall record for the region.